2020
DOI: 10.1002/jbmr.4445
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast-Specific Wnt Secretion Is Required for Skeletal Homeostasis and Loading-Induced Bone Formation in Adult Mice

Abstract: Wnt signaling is critical to many aspects of skeletal regulation, but the importance of Wnt ligands in the bone anabolic response to mechanical loading is not well established. Recent transcriptome profiling studies by our laboratory and others show that mechanical loading potently induces genes encoding Wnt ligands, including Wnt1 and Wnt7b. Based on these findings, we hypothesized that mechanical loading stimulates adult bone formation by inducing Wnt ligand expression. To test this hypothesis, we inhibited … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
(96 reference statements)
0
22
0
Order By: Relevance
“…OsxCreERT2; Wls F/F ; mice were tamoxifen-treated to inactivate Wntless – the Wnt-specific transport receptor responsible for shuttling Wnt ligands to the cell surface for exocytosis 8 – thereby blocking the secretion of all Wnts from osteoblasts and osteocytes. We showed that the periosteal response to tibial loading was 65% lower in Wls knockouts relative to WlsF/F controls, indicating that Wnts produced by osteoblast-lineage cells are important mediators of loading-induced bone formation 7 .…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…OsxCreERT2; Wls F/F ; mice were tamoxifen-treated to inactivate Wntless – the Wnt-specific transport receptor responsible for shuttling Wnt ligands to the cell surface for exocytosis 8 – thereby blocking the secretion of all Wnts from osteoblasts and osteocytes. We showed that the periosteal response to tibial loading was 65% lower in Wls knockouts relative to WlsF/F controls, indicating that Wnts produced by osteoblast-lineage cells are important mediators of loading-induced bone formation 7 .…”
Section: Introductionmentioning
confidence: 80%
“…To achieve this, tamoxifen dissolved in corn oil was delivered by oral gavage for 5 days. We previously used a similar dosing strategy for Cre reporter analysis in 5-month old OsxCreERT2; Rosa-Ai9 mice, which showed robust TdTomato reporter expression on the bone surface (osteoblasts) and throughout the cortical bone (osteocytes) within days of tamoxifen treatment (Lawson, et al 2021) – indicating that OsxCreERT2 targets both osteoblasts and osteocytes in the bones of adult mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations